(untitled) (LEARNing Landscapes, 2015)
The purpose of this article is to describe student experiences when incorporating Twitter into a Bachelor of Education (BEd) course. Data for this participatory action research were gathered from eight first-year BEd students who provided written answers to 16 open-ended questions and participated in two focus group interviews. Findings indicated that, after participants completed a Twitter assignment, their views of Twitter and its applicability in educational realms changed. Analyzed through the emerging concept of new pedagogy, the Twitter experience enhanced collaboration and communication between student and the instructor. An implication is that if BEd students are to effectively incorporate technology into future kindergarten to grade 12 classrooms, they need to experience digital literacy during undergraduate courses.